Investigation of Al-20Sn-10Cu alloy directional solidification by laboratory X-radiography. Issue 1 (1st January 2023) - Reinhart, G; Ngomesse, F; Bertelli, F.; Benigni, P; Campos, A; Nguyen-Thi, H
Abstract: Al-based alloys with a soft phase such as Sn are extensively used for bearing components due to their self-lubricating properties. Al-Sn alloys lack the ability to support heavy loads so the alloying with Cu as a third element provides solution strengthening of the aluminium matrix. A crucial issue in the manufacturing of Al-Sn-Cu alloys is the miscibility gap in the phase diagram of the system. Liquid immiscibility is responsible for severe segregation during the solidification process, due to the large density difference between the Al-rich and Sn-rich liquids, which limits their utilization in industry. It is therefore both scientifically and technically important to accurately understand their solidification path. In the present work, the solidification of a ternary Al-20wt.%Sn-10wt.%Cu alloys was investigated in-situ by using X-radiography. Directional solidification experiments were performed on sheet-like samples in the laboratory device SFINX (Solidification Furnace with IN-situ X-radiography), which consists of a Bridgman-type gradient furnace and an X-radiography system. The solidification sequence was determined based on the observation of the recorded images, enlightening the successive steps of the solidification path. These observations were compared to predictions obtained from thermodynamic calculations. Complementary post-mortem microscopic analyses showed that the dendrite primary trunk and secondary arms developed along <110> crystallographic axes instead of the usually expected <100>.